Sociedade Felupe: Desintegração ou transformação social? - Lúcia Bayan (Cadernos de Estudos Africanos)
This paper aims to analyse some of the changes and social transformations occurred in recent years in the internal dynamics of the Felupe (or Joola-ajamaat), an agrarian society in the north-west of Guinea-Bissau. Well adapted to the environment, the Felupe have the necessary knowledge and techniques that allowed them to maintain food security and social cohesion for centuries. This society currently faces sudden changes of parameters such as climate changes, world market prices instability or reduction in labour availability. Based on literature review and field work carried out during 2009 and 2012, this paper identifies the strategies adopted by this society to respond to the constraints inherent to the dynamics of globalization.